2016
DOI: 10.1063/1.4949216
|View full text |Cite
|
Sign up to set email alerts
|

Simplified analysis of solar-weighted specular reflectance for mirrors with high specularity

Abstract: Abstract. The most relevant parameter to properly characterize solar mirrors is the solar-weighted near-specular reflectance. As this parameter cannot be directly measured with off-the-shelf instruments, a simplified procedure to be applied for highly specular solar mirrors is proposed in this paper. The approach, based on two criteria, was experimentally employed to check a wide variety of solar reflector materials. Only those mirrors with known high specularity passed the criteria, indicating that the propos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
11
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3
3

Relationship

4
2

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 7 publications
1
11
0
Order By: Relevance
“…Although this approximation is appropriate for reflectors with high specularity in the whole solar spectrum, new research has demonstrated that for some innovative reflector materials a valid and adequate procedure is still missing. Research work of the last few years regarding the reflectance measurement procedure [13]- [15] and instruments [16]- [18] to assess solar reflector materials has advanced significantly.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although this approximation is appropriate for reflectors with high specularity in the whole solar spectrum, new research has demonstrated that for some innovative reflector materials a valid and adequate procedure is still missing. Research work of the last few years regarding the reflectance measurement procedure [13]- [15] and instruments [16]- [18] to assess solar reflector materials has advanced significantly.…”
Section: Introductionmentioning
confidence: 99%
“…It deserves to be mentioned the activities ongoing in several working groups during the last decade to stablish a proper protocol to measure the reflectance of concentrating solar reflector materials. A group of experts in the field of optical characterization of solar reflectors has been working since 2009 as members of the SolarPACES Organization (which belongs to the International Energy Agency, IEA) to create a reflectance measurement guideline [9], [15]. Several versions of the guideline have been already published [10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several agreements reached by this group are collected in a document in which current version is titled "Parameters and method to evaluate reflectance properties of reflector materials for concentrating solar power technology" (hereinafter "SolarPACES Reflectance Guideline") [15]. This document has been used as a reference by the CST community for the last years and it has even been mentioned by the first standard published about solar reflectors' durability testing, the UNE 206016:2018 [16], as the measurement method to assess durability experiments.The measurement protocol described in this guideline, in order to measure new and clean solar reflectors, has proven to be very accurate and easy-to-use for any laboratory or company equipped with conventional commercial instruments [17,18]. However, the proposed conventional method used to characterize aged and/or soiled reflector samples is insufficient and inaccurate since only some specific spots of the samples are assessed and it does not take into consideration θ i and ϕ dependence.…”
mentioning
confidence: 99%
“…The measurement protocol described in this guideline, in order to measure new and clean solar reflectors, has proven to be very accurate and easy-to-use for any laboratory or company equipped with conventional commercial instruments [17,18]. However, the proposed conventional method used to characterize aged and/or soiled reflector samples is insufficient and inaccurate since only some specific spots of the samples are assessed and it does not take into consideration θ i and ϕ dependence.…”
mentioning
confidence: 99%